Kemampuan Berpikir Aljabar dan Concept Image Siswa SMP pada Sistem Persamaan Linear Dua Variabel - Fajriah Fajriah; Novianti Novianti; Husni Rahmah; Fachrurrazy Fachrurrazy (Journal on Education, 2024)
Concept image is not unique, meaning that each individual's representation of the same concept can vary depending on previous experiences. Algebraic thinking ability and concept image need to be studied because they are related. The purpose of this study is to describe the algebraic thinking ability and concept image of junior high school students on the material of the system of linear equations of two variables that students build after obtaining classroom learning. This research uses qualitative research methods with a hermeneutic phenomenological approach which is a study conducted to interpret a meaning obtained by a person towards an experience. This research was conducted at one of the State Junior High Schools 2 Bandar Baru with 30 students participating. Data collection was done through test questions and interviews with students. The results showed that the algebraic thinking process and concept image of students were not optimal, meaning that the concepts owned by students on the material of the system of linear equations of two variables were far from the scientific concept. This is due to students' knowledge of algebraic thinking in the context of mathematical language and mathematical modeling has not been maximally achieved so that it affects students' concept image